Mixed nuts [videorecording (DVD)] - Martin, Steve, 1945-; Kahn, Madeline; Klein, Robert, 1942-; LaPaglia, Anthony; Lewis, Juliette; Reiner, Rob; Sandler, Adam; Wilson, Rita; Ephron, Nora; Ephron, Nora; Balasko, Josiane (Columbia TriStar Home Entertainment, 2001)
A wild and wacky comedy about oddball characters in Los Angeles at Christmastime, centered around a suicide hotline service.